Meropenem to Treat Valproic Acid Intoxication. Issue 3 (June 2022) - Smolders, Elise J.; Ter Heine, Rob; Natsch, Stephanie; Kramers, Kees
Abstract: This therapeutic drug monitoring (TDM) grand round describes a patient with serious valproic acid intoxication. A total valproic acid level of 844 mg/L and an unbound valproic acid level of 604 mg/L were observed. Meropenem was administered to enhance the clearance of valproic acid. This off-label usage of meropenem is based on the drug–drug interaction between carbapenems and valproic acid, which reduced the level of valproic acid within 24 hours after administration.